Integrating Clean Water Provision, Environmental Recovery, and Disaster Education in Post-Disaster Community Empowerment - Ahmad Noufal Akram; Taufiq C. Dawood; Endang Pitaloka; Syahriyal; Fakhrurrazi; Diana Setya Ningsih; Siti Aminah; Khairil Umuri; Teuku Muhammad Syahrizal; Muftahuddin; Najla; Ledy Mahara Ginting; Miftahuddin (Universitas Syiah Kuala, 2026)
This community service program addressed the limited access to clean water, environmental sanitation problems, and low disaster preparedness among communities affected by hydrometeorological disasters in Rancong Village, Kuta Blang District, Bireuen Regency. The program aimed to improve clean water access, restore the post-disaster living environment, strengthen disaster mitigation awareness, and support village administration through community data collection and mapping. A participatory community empowerment method was applied through field observation, informal interviews, community discussions, clean-up activities, installation of a clean water facility, disaster mitigation education, psychosocial activities for children, population data collection, and village mapping. The program was implemented from 2 to 21 February 2026 with a total of 207 effective student working hours. The results showed that the clean water installation was successfully used by the community, public facilities and residential areas became cleaner and safer, children gained basic disaster mitigation knowledge, and a village map was produced to support local planning.